PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK SUKARDI HASAN DAN REKAN) - Supriadi, Holili; Herlambang, Iqbal; Hastuti, Wedia; Adhani, Ida (Accounting Research and Business Journal, 2025)
This study aims to test and determine the effect of Competence and Independence on Audit Quality at the Public Accounting Firm of Sukardi Hasan and Partners. The variables in this study are: (1) Dependent Variable, namely Audit Quality, and (2) Independent Variable: Competence and Independence of the auditor. The population in this study is at the Public Accounting Firm of Sukardi Hasan and Partners. The data used in this study are primary data obtained from data collection using a questionnaire. The selection of research samples uses a simple random sampling technique with a sample of 31 respondents. The analysis methods used are normality test, heteroscedasticity test, multiple linear regression analysis, F-statistic test, t-statistic test, and determination coefficient test through the Statistical Package for Social Sciences (SPSS) version 23 program. Based on the results of the F-statistic test, the significance value is 0.039, which is below 0.05. Thus, simultaneously, Auditor Competence and Independence have a significant effect on Audit Quality at the public accounting firm of Sukardi Hasan and Partners.